A Preliminary Study of Cardiovascular Risk Factor Epidemiology in Desk Job Workers: The HDD Study (Hypertensive, Diabetes & Dyslipidaemia) - Jaiswal, Rajendra Prasad; Mishra, Prabhakar Bhushan; Bhushan, Bharat (Student’s Journal of Health Research Africa, 2024)
Background: The urban Indian population has a higher death rate from cardiovascular disease (CVD), a drawback of industrialization and urbanization. A preliminary investigation into the epidemiology of the three main CVD risk factors— Hypertension, Diabetes & Dyslipidaemia (HDD) among desk job workers was the aim of this study. Materials and Methods: Utilizing medical records from a week-long on-site medical health screening camp, a retrospective analysis was conducted. A statistical analysis was subsequently performed to compare the BMI and specific behavioural-demographic characteristics (age, gender, smoking, and alcohol consumption status) between the groups with and without HDD. Results: HDD prevalence was 12.9%, 7.4%, and 14.4%, in that order. The presence of hypertension appears to be associated with age, gender, BMI, and alcohol use, whereas the presence of diabetes is associated with age and BMI alone, and the presence of dyslipidaemia is associated with age, gender, and smoking status. Conclusion: It emphasizes the necessity of a robust public health education program that promotes and instil healthy lifestyle choices, such as consistent exercise and a nutritious, balanced diet, in the populace to help them control their weight and, ultimately, lessen the burden of chronic diseases both domestically and internationally.